The elusive tidal tails of the Milky Way globular cluster NGC 7099 - Piatti, Andres Eduardo (2020)
We present results on the extra-tidal features of the Milky Way globular cluster NGC 7099, using deep gr photometry obtained with the Dark Energy Camera (DECam). We reached nearly 6 mag below the cluster's main sequence (MS) turnoff, so that we dealt with the most suitable candidates to trace any stellar structure located beyond the cluster tidal radius. From star-by-star reddening corrected color-magnitude diagrams (CMDs), we defined four adjacent strips along the MS, for which we built the respective stellar density maps, once the contamination by field stars was properly removed. The resulting, cleaned, field star stellar density maps show a short tidal tail and some scattered debris. Such extra-tidal features are hardly detected when much shallower Gaia DR2 data sets are used and the same CMD field star cleaning procedure is applied. Indeed, by using 2.5 mag below the MS turnoff of the cluster as the faintest limit (G < 20.5 mag), cluster members turned out to be distributed within the cluster's tidal radius, and some hints for field star density variations are found across a circle of radius 3.5° centered on the cluster and with similar CMD features as cluster stars. The proper motion distribution of these stars is distinguishable from that of the cluster, with some superposition, which resembles that of stars located beyond 3.5° from the cluster center.